The Effect of EPS and DER on Stock Price with Dividend Policy as an Intervening Variable - Siregar, Emi Sari Sulastri; Mintarti, Sri (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This study aims to find out whether there is a relationship between independent variables in the form of Earning per Share, and Debt To Equity Ratio with Dependent variables in the form of Stock Price with Dividend Policy as Intervening Variables in manufacturing companies listed on the Indonesia Stock Exchange. The population of this study is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in the period 2017 – 2022. Based on the specified sample criteria, 102 data were obtained from 17 companies. The data analysis in this study was carried out by descriptive analysis and inferential statistical analysis using the Partial Least Squares Structural Equation Modeling (PLS SEM) technique using SmartPLS 3.0 software. The results of the study show that Earning Per Share has a significant and positive effect on Dividend Policy, Earning Per Share has a significant and positive effect on Stock Price, Debt To Equity Ratio has a significant and positive effect on Dividend Policy, Debt To Equity Ratio does not have a significant effect on Stock Price, Dividend The policy does not have a significant effect on the stock price, and the dividend policy is not able to moderate the Earnings Per Sahre and the Debt to Equity Ratio to the stock price